Sosialisasi Bahaya Narkoba dan Bantuan Hukum sebagai Program Peningkatkan Kesadaran Hukum di Desa Jagara - Asri Apriliani; Bakrie Mandela; Sarip Hidayat; Suwari Akhmaddhian (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Legal counseling is a preventative measure to increase public legal awareness, particularly regarding legal aid and anticipating drug abuse. Legal aid is a crucial instrument in ensuring access to justice for the underprivileged, as mandated by Law Number 16 of 2011 concerning Legal Aid. This counseling provides an understanding of legal rights, procedures for obtaining legal aid, and the role of legal aid institutions in assisting people facing legal issues. Furthermore, the counseling also highlights the dangers of narcotics and strategies for preventing and addressing them. With the increasing number of drug abuse cases among various groups, effective education is needed regarding the negative impacts of drugs, legal sanctions governing abuse, and the active role of families and communities in preventing drug distribution. Through this legal counseling in Jagara Village, Darma District, Kuningan Regency, it is hoped that the community will have a better understanding of their legal rights, increase awareness in utilizing legal aid appropriately, and be able to contribute to drug abuse prevention efforts. This aims to create a safer, more orderly, and more just environment for all levels of society.